Corporate Identity Tagline "Radionya Urang Bandung" Urban Radio - Fauzie, Ahmad Faqih; Rosyidi, Imron; Nur Chidayah, Prita Priantini (Reputation: Jurnal Ilmu Hubungan Masyarakat, 2023)
Corporate identity is a very important element and plays a big role in the development of Urban Radio. This research aims to find out about Urban Radio's Corporate Identity Tagline "Radionya Urang Bandung". The stages carried out are the Recognition, Recall and Top of Mind stages. This research uses a qualitative approach, with descriptive methods, and a constructivist paradigm. Data collection was carried out using passive participant observation techniques and in-depth interviews. the process of introducing the corporate identity of Urban Radio's tagline "Radionya Urang Bandung" is (1) recognition, (2) Recall, and (3) top of mind. Urban Radio has gone through stages in accordance with the Brand Awareness concept, namely the Recognition, Recall and Top of Mind stages.